Study of environmentally friendly and facile functionalization of graphene nanoplatelet and its application in convective heat transfer. (15th October 2017) - Sadri, Rad; Hosseini, Maryam; Kazi, S.N.; Bagheri, Samira; Ahmed, S.M.; Ahmadi, Goodarz; Zubir, Nashrul; Sayuti, Mohd; Dahari, Mahidzal
Highlights: Highly stable nanofluid was synthesized by an eco-friendly functionalization method. The success of functionalization process was verified by characterization techniques. Remarkable thermo-physical properties and heat transfer coefficient were obtained. Abstract: The chemical functionalization of carbon-based nanomaterial typically involves toxic and corrosive inorganic acids that are harmful to environment and human health. In this study, an environmentally friendly, facile and cost effective procedure for synthesizing a novel and highly dispersed functionalized graphene nanoplatelets (GNPs) nanofluids for use as a heat transfer fluids was developed. In the new approach, GNPs were functionalized covalently with Gallic Acid (GA) in a one-pot free radical grafting method. The Gallic acid-treated graphene nanoplatelets (GAGNPs) were dispersed in distilled water (DI water) with different weight concentrations to prepare GAGNPs-water nanofluids (nano-coolants). The effectiveness of the functionalization process was verified by the Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and transmission electron microscopy (TEM). The UV–visible absorption spectroscopy was used to show a sustained stability of nanoparticles. Thermo-physical and rheological properties of GAGNPs aqueous suspensions with different weight concentrations were experimentally investigated. This was followed by measurement of the convective heat transfer coefficient, Nusselt number and friction factor for fully developed turbulent flow of GAGNPs nanofluids at a constant heat flux. The experimental results were compared with those of the base fluid. The GAGNPs nanofluids showed a significant increase in the convective heat transfer coefficient and Nusselt number, while the increases in the friction factor and pumping power were small. Furthermore, the comparison showed that the overall performance index was higher than 1. The novel and eco-friendly GAGNPs nanofluids have the potential to be used as highly effective working fluids for various heat transfer applications.